2011
DOI: 10.1002/hep.24524
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid CB2 receptors protect against alcoholic liver disease by regulating Kupffer cell polarization in mice

Abstract: Activation of Kupffer cells plays a central role in the pathogenesis of alcoholic liver disease. Because cannabinoid CB2 receptors (CB2) display potent anti-inflammatory properties, we investigated their role in the pathogenesis of alcoholic liver disease, focusing on the impact of CB2 on Kupffer cell polarization and the consequences on liver steatosis. Wildtype (WT) mice fed an alcohol diet showed an induction of hepatic classical (M1) and alternative (M2) markers. Cotreatment of alcohol-fed mice with the CB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
193
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(228 citation statements)
references
References 51 publications
(82 reference statements)
16
193
0
4
Order By: Relevance
“…1 Clinical studies have further suggested that the presence of the short (GT)n repeat variant is associated with a reduced risk of cardiovascular or pulmonary disease, among others, whereas conversely, there is an increased risk in patients with the long (GT)n repeat variant. Interestingly, we previously reported that HO-1 is antifibrogenic 2,3 and that induction of HO-1 protects against alcohol-induced liver injury. 4 These data raised the interesting hypothesis that the long (GT)n repeat variant in HO-1 promoter could be associated with the presence and severity of ALD.…”
Section: Replymentioning
confidence: 98%
See 1 more Smart Citation
“…1 Clinical studies have further suggested that the presence of the short (GT)n repeat variant is associated with a reduced risk of cardiovascular or pulmonary disease, among others, whereas conversely, there is an increased risk in patients with the long (GT)n repeat variant. Interestingly, we previously reported that HO-1 is antifibrogenic 2,3 and that induction of HO-1 protects against alcohol-induced liver injury. 4 These data raised the interesting hypothesis that the long (GT)n repeat variant in HO-1 promoter could be associated with the presence and severity of ALD.…”
Section: Replymentioning
confidence: 98%
“…Induction of heme oxygenase-1 (HO-1) was shown to prevent liver fibrosis 1 and ethanol-induced liver damage in mice. 2,3 A functional microsatellite (GT) n repeat variant in the HO-1 promoter region is tightly correlated with inducibility of HO-1 protein expression, i.e., short (<26) (GT) n repeat carriers present increased HO-1-expression-derived antiinflammatory and cytoprotective effects. 4 As opposed to cardiac or pulmonary disease, HO-1 gene polymorphisms in human liver disease have been largely unexplored.…”
mentioning
confidence: 99%
“…A recent study suggested that an antiinflammatory effect of CB1 antagonist SR141716 also may contribute to the favorable effects of CB1 receptor antagonists in the treatment of obesity, nonalcoholic fatty liver disease and closely related features of the metabolic syndrome (41). However, published data in this regard remain contradictory, and only one study addressed the mechanisms of how the ECS intercepts with inflammatory processes (23). In our study, we observed moderately reduced portal inflammation and a lack of COX-2 upregulation in CB1 -/-mice following alcohol exposure, while TNFα and iNOS were not different between CB1 -/-and WT mice, suggesting that the absence of CB1 has little impact on well-established triggers of hepatic inflammation.…”
Section: Cb1mentioning
confidence: 99%
“…Endocannabinoids exert numerous and sometimes opposite effects on liver target cells which could be CB receptor-dependent or independent, and are involved in control of cell survival and apoptosis (18). Thus, AEA induced cell necrosis via several mechanisms, whereas 2-AG induced apoptosis in HSC (10,19,20 (23). However, the extent of and effects on fibrosis by CB1 antagonism in the study by Trebicka et al were small, albeit significant, which could be due to the animal model in which mice received alcohol via drinking water.…”
Section: Introductionmentioning
confidence: 99%
“…Cannabidiol a plant-derived cannabinoid exhibit anti-fibrotic potential preventing proliferation and induces endoplasmic reticulum stress mediated apoptosis in activated HSC [19]. It has been reported that endocannabinoid receptors CB2 agonist JWH-133 reduces fibrosis through promoting apoptosis in activated HSC, liver regeneration, regulating pro-inflammatory macrophage polarization and down regulation of the profibrogenic cytokine IL17 by Th17 lymphocytes [20][21][22][23]. Upon liver injury CCL5 chemokine strongly expressed to recruit inflammatory cells and HSC.…”
Section: Deactivation or Elimination Of Activated Hepatic Stellate Cellsmentioning
confidence: 99%